What Hospital Implementation Strategies Are Associated with Successful Performance Under Maryland's All‐Payer Model?. (20th August 2020) - Perry, R.; Mittman, L.; Elkins, W.; Suvada, K.; Haber, S.
Abstract : In January 2014, Maryland shifted its all‐payer hospital rate setting system from one that paid hospitals based on charges per case to a fixed global budget payment model. Under Maryland's All‐Payer Model (MDAPM), hospitals had considerable flexibility to implement strategies to meet their global budget and other model goals, including improving quality, safety, and patient satisfaction. We conducted a comparative case study to identify the implementation strategies used in hospitals with successful outcomes under MDAPM. We conducted a mixed‐method analysis that examined the association between changes in hospital performance and the use of different implementation strategies. We used data from a survey fielded among all Maryland acute care hospitals from October to December 2018 that examined whether hospitals implemented 28 strategies, either before or during MDAPM. We complemented survey data with qualitative data collected from site visits to all hospitals and focus group discussions with hospital‐based nurses and physicians conducted from April 2015 to February 2019. We calculated two hospital‐level measures to assess performance—operating margin (financial performance) and Medicare 30‐day unplanned readmission rate (patient care performance). We used hospital financial reports to calculate change in operating margin from a two‐year baseline period (FY2012‐FY2013) to a five‐year implementation timeframe (FY2014‐FY2018). For readmissions, we calculated the change from a three‐year baseline period (January 2011‐December 2013) to a 4.5‐year implementation timeframe (January 2014‐June 2018). We established four performance categories for each outcome based on a hospital's pre‐post change: decline and low, medium, or high improvement. For financial performance, improvement was an increase in operating margin. For patient care, performance improvement was a decrease in readmissions. Cut points for low, medium, and high improvement were based on the distribution of each outcome. 46 Maryland acute care hospitals. Two strategies—employing physician staff and providing patients with clinically specific education—were associated with improvements in both performance outcomes. Eight strategies were associated with improved patient care performance, such as utilizing customized data analytics, engaging physicians in implementing MDAPM‐related strategies, investing in interventions that address social determinants of health, and referring patients to alternative care settings. Three strategies were associated with improved financial performance, including using Maryland's health information exchange and participating in a program to improve alignment with physicians. Six strategies were not associated with either performance measure. Eight strategies were employed by nearly all Maryland hospitals and, therefore, could not be associated with hospital performance. Almost half of the strategies examined were associated with at least one of the dimensions of successful performance examined. The comparative case study approach does not provide a causal perspective on hospital performance. Thus, we cannot determine whether adopting these strategies improved hospital performance or whether improvements in performance facilitated hospitals' ability or desire to implement these strategies. Hospitals seeking to improve their performance may want to emphasize the two implementation strategies that were associated with greater success in both patient care and financial performance. Hospitals operating under a global budget model may consider adopting the eight strategies implemented by nearly all Maryland hospitals as implementation building blocks. Centers for Medicare and Medicaid Services.